A Study on Doped Heterojunctions in TiO2 Nanotubes: An Efficient Photocatalyst for Solar Water Splitting. Issue 1 (December 2017) - Preethi, L.; Antony, Rajini; Mathews, Tom; Walczak, Lukasz; Gopinath, Chinnakonda
Abstract The two important factors that affect sunlight assisted water splitting ability of TiO2 are its charge recombination and large band gap. We report the first demonstration of nitrogen doped triphase (anatase-rutile-brookite) TiO2 nanotubes as sun light active photocatalyst for water splitting with high quantum efficiency. Nitrogen doped triphase TiO2 nanotubes, corresponding to different nitrogen concentrations, are synthesized electrochemically. Increase in nitrogen concentration in triphase TiO2 nanotubes is found to induce brookite to anatase phase transformation. The variation in density of intra-band states (Ti3+ and N 2p states) with increase in nitrogen doping are found to be critical in tuning the photocatalytic activity of TiO2 nanotubes. The presence of bulk heterojunctions in single nanotube of different nitrogen doped TiO2 samples is confirmed from HRTEM analysis. The most active nitrogen doped triphase TiO2 nanotubes are found to be 12 times efficient compared to pristine triphase TiO2, for solar hydrogen generation. The band alignment and charge transfer pathways in nitrogen doped TiO2 with triphase heterojunctions are delineated. Bulk heterojunctions among the three phases present in the nanotubes with intra-band defect states is shown to enhance the photocatalytic activity tremendously. Our study also confirms the theory that three phase system is efficient in photocatalysis compared to two phase system.